Indian land grants record
Record of Indian land grants in Georgia, New York State, and Pennsylvania by Choctaw Indians, Creek Indians, Delaware Indians, and others to the colonial governments.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Choctaw Indians; Creek Indians; Delaware Indians; Indians of North America -- Land tenure; Indians of North America -- Georgia; Indians of North America -- New York (State); Indians of North America -- Pennsylvania